Behavioral responses of male elk to hunting risk. Issue 3 (11th January 2022) - Smith, Joshua B.; Spitz, Derek B.; Brown, Casey L.; Wisdom, Michael J.; Rowland, Mary M.; Forrester, Tavis D.; Johnson, Bruce K.; Clark, Darren A.
Abstract: Prey respond to predation risk with a range of behavioral tactics that can vary based on space use and hunting mode of the predator. Unlike other predators, human hunters are often more spatially and temporally restricted, which creates a period of short‐duration, high‐intensity predation risk for prey. Consequently, identifying the roles different hunting modes (i.e., archery and rifle), hunts for targeted and non‐targeted species, and landscape features play in altering spatial and temporal responses of prey to predation risk by humans is important for effective management of harvested populations. From 2009 to 2016, we used a large‐scale experiment including 50 animal‐years of location data from 38 unique male elk ( Cervus canadensis ) to quantify changes in movement and resource selection in response to hunters during 3 separate 5‐day controlled hunts for antlered males (elk archery, deer [ Odocoileus spp.] rifle, and elk rifle) at the Starkey Experimental Forest and Range in northeast Oregon, USA. We evaluated competing hypotheses regarding elk responses to varying levels of prey risk posed by the different hunt types. We predicted that the strength of elk behavioral responses would increase with perceived hunter lethality (i.e., weak response to elk archery but similar response to elk and deer rifle hunts) and that prey response would be closely associated with hunter activity within the diel cycle (greater during diurnal than nocturnal hours) and across hunting seasons. Elk responses were strongest during diurnal hours when hunters were active on the landscape and were generally more pronounced during both rifle hunts than during the archery hunt (supporting our perceived lethality hypothesis). Male elk avoided open roads across all periods except during nocturnal hours of the breeding season and alternated between avoidance of areas with high canopy cover during nocturnal hours and selection during diurnal hours. In combination these patterns led to distinct distributional changes of male elk from pre‐hunt to hunt periods. Patterns of male elk selection highlight the importance of managing for heterogeneous landscapes to meet a variety of habitat, harvest, hunter satisfaction, and escapement objectives. Abstract : Our results illustrate male elk exhibit strong changes in resource selection and movement rates based on real (elk archery, elk rifle) and perceived (deer rifle) hunting risk yet vary across the diel cycle. Patterns of selection we observed highlight the need to manage for heterogeneous landscapes to ensure elk have adequate foraging opportunities and secure habitats to meet daily requirements during hunting seasons.